2020
DOI: 10.1088/1755-1315/443/1/012081
|View full text |Cite
|
Sign up to set email alerts
|

Moderate pretreatment strategies for improvement of reducing sugar production from oil palm empty fruit bunches

Abstract: Pretreatment at mild condition is the strategy to minimize energy consumption, to reduce toxic compounds influencing to further process, and to obtain the high reducing sugar yield as fermentation substrate from cellulose and hemicellulose of oil palm empty fruit bunches (OPEFB). The yield still could be increased by optimizing pretreatment condition and varying several process alternatives. In this study, the effect of acetic acid addition and its corresponding concentration (5–15%), pretreatment temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The same trend was observed for hemicellulose composition in both U‐EPFG and G‐EPFG where the longer pre‐treatment time does not alter the structure of the biomass significantly, shown by negligible changes in the composition values. The results of this study were also reflected by studies conducted by Harahap et al., [ 21 ] where they observed that no significant difference of glucose concentration was produced at different pre‐treatment times when treating oil palm empty fruit bunch using the mild hydrothermal method. Therefore, in a mild hydrothermal pre‐treatment of a starch‐lignocellulosic biomass, further pre‐treatment time does not affect biomass structural changes, hence, it is unnecessary to prolong the pre‐treatment time that demands more energy.…”
Section: Resultssupporting
confidence: 84%
“…The same trend was observed for hemicellulose composition in both U‐EPFG and G‐EPFG where the longer pre‐treatment time does not alter the structure of the biomass significantly, shown by negligible changes in the composition values. The results of this study were also reflected by studies conducted by Harahap et al., [ 21 ] where they observed that no significant difference of glucose concentration was produced at different pre‐treatment times when treating oil palm empty fruit bunch using the mild hydrothermal method. Therefore, in a mild hydrothermal pre‐treatment of a starch‐lignocellulosic biomass, further pre‐treatment time does not affect biomass structural changes, hence, it is unnecessary to prolong the pre‐treatment time that demands more energy.…”
Section: Resultssupporting
confidence: 84%
“…The study reported by also had proven that the increase of acid concentration, time, and temperature significantly influenced the decrease of reducing sugars, including xylose, for other acids type such as oxalic, formic, and citric acid [39]. proposed twostage treatment to optimize the reducing sugar yield at the mild condition [40].…”
Section: A Hydrolysate Compositionmentioning
confidence: 99%
“…This material is previously just converted to the heat and power generation or several products such as compost and mulch. Unfortunately, the rest 142 of this materials is still available in huge amount and needs other conversions to higher valuable products [1]. The OPEFB consisted of 36.59-43.54% cellulose, 19.14-24.97% hemicellulose, and 19.83-26.53% lignin [2][3][4][5] in which those components could still be utilized to produce high-added value products.…”
Section: Introductionmentioning
confidence: 99%